Optimization Study on the Comfort of Human-Seat Coupling System in the Cab of Construction Machinery - Cheng, Lei; Wen, Hansheng; Ni, Xiangyu; Zhuang, Chao; Zhang, Wenjian; Huang, Haibo (Machines (Basel), 2023)
The seat of a construction machinery cab is used as the research object. For the current human-seat coupling system comfort research methods and optimization index deficiencies, the seat body pressure comfort and vibration comfort at the same time optimized. Based on the more specialized Toyota 50 percentile dummy model, a human-seat finite element simulation model is established, and the body pressure distribution and vibration response are simulated and calculated. The transverse and longitudinal pressure distributions of the backrest and seat cushion and the pressure map are used to verify the simulation model’s body pressure comfort evaluation indexes. At the same time, the vibration response test is used to verify the vibration comfort evaluation indexes of the simulation model. The test results show that the accuracy of each evaluation index of the established coupling model is greater than 85%, which can provide model support for the subsequent optimization work. In order to improve the comfort of the seat of construction machinery during operation, the hardness of the upper sponge and lower layer sponge is reduced and increased by 10% and 15%, respectively, on the original seat. The body pressure comfort evaluation indexes of the ischium peak pressure, ischium mean pressure, thigh peak pressure and thigh mean pressure are used to evaluate the improved seat. The proposed optimization scheme is to reduce the hardness of the upper sponge and lower layer sponge of the seat cushion by 10% to improve the seat body pressure comfort. Finally, the evaluation indexes of body pressure comfort and vibration comfort are verified by four subjects in an improved seat, and the cushion pressure of different subjects is reduced while the vibration isolation rate is increased, which shows the rationality of the proposed optimization scheme. In addition, the evaluation results of the improved seat are different for subjects of different body sizes, with the most significant improvement for the subject of greater height and weight. The modeling and comfort evaluation methods adopted in the paper can provide a reference for the design and development of the seat.